Theoretical foundations of web site interface usability assessment - Kozel, O.; Kolesnykov, D.; Nazarov, O.; Nazarova, N. (ХНУРЕ, 2023)
ВThis paper presents how to redesign a website by applying a set of design principles to enhance the usability. The main objectives of the study are to find out the usability problems of the targeted interactive system in order to list out required suggestions to improve the website and to provide solutions by re-designing the existing interactive system. In order to implement the objectives of the project, we should initially evaluate the interactive system using usability evaluation. The outcome of the evaluation provides us information about the issues and requirements to design a new system. Based on the evaluation and its outcome, various methods will be used for resolving the problems while re-designing the website. This helps in identifying the problems which require usability improvements. The objective of this paper is to provide a conceptual framework and foundation for systematically investigating features in the Web environment that contribute to user satisfaction with a Web interface and uses motivation-hygiene theory to guide the identification of these features. Objects of research are generative systems with associative memory. Purpose is a development of a system for evaluating the hierarchy and heterogeneity of the interface of web pages using neural network technologies. У цій статті представлено, як переробити веб-сайт, застосувавши набір принципів дизайну для покращення юзабіліті. Основними цілями дослідження є з'ясування проблем юзабіліті цільової інтерактивної системи для того, щоб сформулювати необхідні пропозиції щодо покращення веб-сайту та запропонувати рішення шляхом редизайну існуючої інтерактивної системи. Для того, щоб реалізувати цілі проекту, ми повинні спочатку оцінити інтерактивну систему за допомогою оцінки юзабіліті. Результати оцінки нададуть нам інформацію про проблеми та вимоги до проектування нової системи. На основі оцінки та її результатів будуть використані різні методи для вирішення проблем під час редизайну веб-сайту. Це допомагає виявити проблеми, які потребують покращення юзабіліті. Метою цієї статті є створення концептуальної основи для систематичного дослідження особливостей веб-середовища, які сприяють задоволеності користувачів веб- інтерфейсом, а також використання теорії мотивації та гігієни для визначення цих особливостей. Об'єктом дослідження є генеративні системи з асоціативною пам'яттю. Метою роботи є розробка системи оцінки ієрархічності та гетерогенності інтерфейсу веб-сторінок з використанням нейромережевих технологій.
Keywords: neural network; machine learning; memory; generation; generative models; text; генеративні моделі; генеративні моделі